A new technique for measurement of water permeability of stomatous cuticular membranes isolated from Hedera helix leaves - Santrůcek, J; Simánová, Eva; Karbulková, Jana; Simková, Marie; Schreiber, Lukas (Journal of experimental botany, 2004)
Transpiration of cuticular membranes isolated from the lower stomatous surface of Hedera helix (ivy) leaves was measured using a novel approach which allowed a distinction to be made between gas phase diffusion (through stomatal pores) and solid phase diffusion (transport through the polymer matrix membrane and cuticular waxes) of water molecules. This approach is based on the principle that the diffusivity of water vapour in the gas phase can be manipulated by using different gases (helium, nitrogen, or carbon dioxide) while diffusivity of water in the solid phase is not affected. This approach allowed the flow of water across stomatal pores ('stomatal transpiration') to be calculated separately from the flow across the cuticle (cuticular transpiration) on the stomatous leaf surface. As expected, water flux across the cuticle isolated from the astomatous leaf surface was not affected by the gas composition since there are no gas-filled pores. Resistance to flux of water through the solid cuticle on the stomatous leaf surface was about 11 times lower than cuticular resistance on the astomatous leaf surface, indicating pronounced differences in barrier properties between cuticles isolated from both leaf surfaces. In order to check whether this difference in resistance was due to different barrier properties of cuticular waxes on both leaf sides, mobility of 14C-labelled 2,4-dichlorophenoxy-butyric acid 14C-2,4-DB) in reconstituted cuticular wax isolated from both leaf surfaces was measured separately. However, mobility of 14C-2,4-DB in reconstituted wax isolated from the lower leaf surface was 2.6 times lower compared with the upper leaf side. The significantly higher permeability of the ivy cuticle on the lower stomatous leaf surface compared with the astomatous surface might result from lateral heterogeneity in permeability of the cuticle covering normal epidermal cells compared with the cuticle covering the stomatal cell surface.
Keywords: biologické modely; Cell Membrane Permeability; difuzní komory kultivační; Plant Epidermis; listy rostlin; Plant Transpiration; Microscopy, Electron, Scanning; permeabilita buněčné membrány; mikroskopie elektronová rastrovací; Models, Biological; Hedera; Plant Leaves; Algorithms; voda; Diffusion Chambers, Culture; Water; břečťan; algoritmy; epidermis rostlin; transpirace rostlin